Association Between Graft Type and Risk of Repeat Revision Anterior Cruciate Ligament Reconstruction: A Cohort Study of 1747 Patients. Issue 6 (May 2023) - Heffner, Michael; Chang, Richard N.; Royse, Kathryn E.; Ding, David Y.; Maletis, Gregory B.
Background: With an increasing number of primary anterior cruciate ligament reconstructions (ACLRs), the burden of revision ACLR (rACLR) has also increased. Graft choice for rACLR is complicated by patient factors and the remaining available graft options. Purpose: To examine the association between graft type at the time of rACLR and the risk of repeat rACLR (rrACLR) in a large US integrated health care system registry while accounting for patient and surgical factors at the time of revision surgery. Study Design: Cohort study; Level of evidence, 3. Methods: Data from the Kaiser Permanente ACLR registry were used to identify patients who underwent a primary isolated ACLR between 2005 and 2020 and then went on to have rACLR. Graft type used at rACLR, classified as autograft versus allograft, was the exposure of interest. Multivariable Cox proportional hazard regression was used to evaluate the risk of rrACLR, with ipsilateral and contralateral reoperation as secondary outcomes. Models included factors at the time of the rACLR (age, sex, body mass index, smoking status, staged revision, femoral fixation, tibial fixation, femoral tunnel method, lateral meniscal injury, medial meniscal injury, and cartilage injury) and a factor from the primary ACLR (activity at injury) as covariates. Results: A total of 1747 rACLR procedures were included. The crude cumulative rrACLR incidence at 8-year follow-up was 13.9% for allograft and 6.0% for autograft. Cumulative ipsilateral reoperation incidence at 8-year follow-up was 18.3% for allograft and 18.9% for autograft; contralateral reoperation cumulative incidence was 4.3% for allograft and 6.8% for autograft. With adjustment for covariates, a 70% lower risk for rrACLR was observed for autograft compared with allograft (hazard ratio [HR], 0.30; 95% CI, 0.18-0.50; P < .0001). No differences were observed for ipsilateral reoperation (HR, 1.05; 95% CI, 0.73-1.51; P = .78) or contralateral reoperation (HR, 1.33; 95% CI, 0.60-2.97; P = .48). Conclusion: The use of autograft at rACLR was associated with a 70% lower risk of rrACLR compared with allograft in this cohort from the Kaiser Permanente ACLR registry. When accounting for all reoperations outside of rrACLR after rACLR, the authors found no significant difference in risk between autograft and allograft. To minimize the risk of rrACLR, surgeons should consider using autograft for rACLR when possible.